2012
DOI: 10.3109/00207454.2012.742895
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Premedication Attenuates Isoflurane Anesthesia-Induced β-Amyloid Generation and Cholinergic Dysfunction in the Hippocampus of Aged Rats

Abstract: Melatonin plays an important role in aging and relevant neurodegeneration as an antioxidant and neuroprotector. It can interact with β-amyloid (Aβ) generation, inhibit formation of β-sheet and amyloid fibrils, modulate apoptosis, and protect cholinergic system function in Alzheimer's disease animal model. Recently, its effects on anesthetic-induced neurodegeneration have received more attention, and in this investigation, we explored whether melatonin can attenuate Aβ(1-40) generation and cholinergic dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Cell and animal studies have gone some way in showing some potentially damaging effects of certain anaesthetics, for example, inhalational anaesthetics such as isoflurane and sevoflurane 5, 6, 7, 8, 9, 10. In contrast, the intravenous anaesthetic, propofol, may have largely protective effects 6, 11, 12, 13, mainly shown in animal and cellular models, although it has also been suggested to have some negative actions 14.…”
Section: Introductionmentioning
confidence: 99%
“…Cell and animal studies have gone some way in showing some potentially damaging effects of certain anaesthetics, for example, inhalational anaesthetics such as isoflurane and sevoflurane 5, 6, 7, 8, 9, 10. In contrast, the intravenous anaesthetic, propofol, may have largely protective effects 6, 11, 12, 13, mainly shown in animal and cellular models, although it has also been suggested to have some negative actions 14.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that dietary restriction may change melatonin production and secretion and can also shift the production and secretion time of melatonin when the SCN clock is lacking (18). Owing to the welldescribed neuroprotective effects of melatonin in some studies (19)(20)(21)(22)(23) and the fact that melatonin level is declined in aging and specially in Alzheimer's (17), there seem to be at least some dietary restriction effects related to melatonin level changes. To investigate such a hypothesis, melatonin receptors (MT1, MT2) antagonist (luzindole) was used.…”
Section: Discussionmentioning
confidence: 99%
“…Restricted feeding restores not only a rhythmic transcription of the rate-limiting enzyme for melatonin biosynthesis [aryl-alkylamine-Nacetyl-transferase (AANAT)] but also a rhythmic synthesis of melatonin in the pineal gland (18). Neuroprotective effects of melatonin have been shown in several studies (19)(20)(21)(22)(23). Many studies have reported disrupted circadian rhythms and melatonin production in aging and in Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Isoflurane exposure was performed as previously described [9,15] . In brief, animals were placed in a transparent anesthetic c hamber resting in a temperaturecontrolled water bath (38°C).…”
Section: Isofl Urane Exposurementioning
confidence: 99%
“…Nevertheless, increasing numbers of animal studies have indicated that inhalation anesthetics, such as isoflurane, may cause or increase the risk of developing POCD [7,8] . Specifically, inhalation anesthetics may alter cognitive function via NF-κB-dependent neuroinflammation [9,10] , amyloid β ( Aβ) accumulation [8,[11][12][13] , tau phosphorylation [13,14] , modified neurotransmission [15] and deregulated calcium homeostasis [16] . Among these, the fi rst three appear to be the shared pathological markers of AD, thereby implying an emerging link between POCD and dementia.…”
Section: Introductionmentioning
confidence: 99%